Superior Vena Cava Stenting Guided by Alternative Imaging Modalities in a Patient with Severe Contrast Allergy: A Case Report and Brief Literature Review. (30th June 2013) - Pillutla, Priya; Reardon, Leigh C.; Aboulhosn, Jamil A.
Abstract Major adverse reactions to iodinated radiocontrast media are an uncommon but serious complication of cardiac catheterizations. We present a case of a 52‐year‐old woman with a sinus venosus atrial septal defect and partial anomalous pulmonary venous connection status post repair who presented with superior vena cava graft obstruction. Two overlapping stents were placed within the superior vena cava using gadolinium, CO2 angiography and transesophageal echocardiography for visualization of the graft stenoses. No iodinated media were used.